Income receipt and mortality: Evidence from Swedish public sector employees - Elvira Andersson; Petter Lundborg; Johan Vikström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
In this paper, we study the short-run effect of salary receipt on mortality among Swedish public sector employees. By using data on variation in paydays across work-places, we completely control for mortality patterns related to, for example, public holidays and other special days or events coinciding with paydays and for general within-month and within-week mortality patterns. We find a dramatic increase in mortality on the day salaries arrive. The increase is especially pronounced for younger workers and for deaths due to activity-related causes such as heart conditions and strokes. Additionally, the effect is entirely driven by an increase in mortality among low income individuals, who are more likely to experience liquidity constraints. All things considered, our results suggest that an increase in general economic activity on salary receipt is an important cause of the excess mortality.
Keywords: D91; H31; H55; I10; I12; I38; 330; income; mortality; health; consumption; liquidity constraints; permanent income hypothesis